Complexes of 2,6_diacetylpyridine-di-(1R)_(-)_fenchone diazine (fench=NN=CMe)2C5H5N) ligand with molybdenum, tungsten or palladium - Mustaffa Ahmad (Tanjong Malim, 2011)
Complexes of 2,6_diacetylpyridine-di-(1R)_(-)_fenchone diazine (fench=NN=CMe)2C5H5N) ligand with molybdenum, tungsten or palladium by Mustaffa Ahmad